Mechanical Ventilator and Oxygen Concentrator System: Tinki’s Proof of Concept - Quispe, P.; Gómez-Alzate, D.; Pérez-Buitrago, S. (Springer Science and Business Media Deutschland GmbH, 2024)
The last two years have not only revealed profound deficiencies of the Peruvian health system, but have also led to its collapse on more than one occasion. Within this, medical oxygen production suffered serious problems which led to the shortage of this gas, widely used in mechanical ventilation of patients with respiratory diseases like COVID-19. Given this context, new alternative solutions must aim to eliminate reliance on conventional oxygen sources, therefore, oxygen concentrators were considered to be used as source of mechanical ventilators. In agreement with other studies, this work aims to evaluate the feasibility of a system that couples a MASI mechanical ventilator with COVOX oxygen concentrator, called the Tinki system, in terms of the fraction of inspired oxygen (FiO2). For flows grater than 7 L/min, (FiO2) levels above 80% were obtained. The continuous change of valves and the use of Pressure control mode for ventilation, ensure around 92% in comparison to other set-ups, behaviour that can be maintained over 6 h. Although the results are encouraging, further research is required.
Keywords: Proof of concept; Concentrator; Computer science; Operating system; Telecommunications; https://purl.org/pe-repo/ocde/ford#2.02.00